2013
DOI: 10.1111/tri.12032
|View full text |Cite
|
Sign up to set email alerts
|

The extent of HLA-DR expression on HLA-DR+Tregs allows the identification of patients with clinically relevant borderline rejection

Abstract: Summary Regulatory T cells (Tregs) were shown to be involved into the pathogenesis of acute rejection after transplantation. The suppressive activity of the total regulatory T cell pool depends on its percentage of highly suppressive HLA‐DR+‐Treg cells. Therefore, both the suppressive activity of the total Treg pool and the extent of HLA‐DR expression of HLA‐DR+‐Tregs (MFI HLA‐DR) were estimated in non transplanted volunteers, patients with end‐stage renal failure (ESRF), healthy renal transplant patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In particular, the DR high+ memory Tregs were found to be of potential importance for the suppressive activity of the total Treg pool, as these cells were shown to be reduced significantly in kidney transplant patients with acute rejection, compared to non-rejecting patients [23,24]. Surprisingly, we found this relation to be reversed in pregnancy.…”
Section: Cd25mentioning
confidence: 56%
See 1 more Smart Citation
“…In particular, the DR high+ memory Tregs were found to be of potential importance for the suppressive activity of the total Treg pool, as these cells were shown to be reduced significantly in kidney transplant patients with acute rejection, compared to non-rejecting patients [23,24]. Surprisingly, we found this relation to be reversed in pregnancy.…”
Section: Cd25mentioning
confidence: 56%
“…Especially for Treg cells, it was shown that the highly activated DR low+ and DR high+ memory Tregs have the highest sup-pressive activity within the total T reg pool in normal healthy control subjects [23]. In particular, the DR high+ memory Tregs were found to be of potential importance for the suppressive activity of the total Treg pool, as these cells were shown to be reduced significantly in kidney transplant patients with acute rejection, compared to non-rejecting patients [23,24]. Surprisingly, we found this relation to be reversed in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…An increased post-transplant sCD30 serum concentration and positive pre-and post-transplant anti-HLA class II reactivities may be useful biomarkers for post-transplant immune monitoring predicting BPAR in pediatric renal transplant recipients [27]. Regulatory T cells (Tregs) were also shown to be involved in the pathogenesis of acute rejection [28]. The determination of the HLA-DR MFI of the HLA-DR(+)-Treg subset allows to discriminate between patients with clinically relevant borderline rejection and patients with subclinical rejection or other causes of transplant failure.…”
Section: Discussionmentioning
confidence: 99%
“…33 HLA-DR 1 Tregs have been previously described as a functionally distinct population with a high suppressive effect that might play a role in organ rejection. [34][35][36] Additionally, earlier publications have shown that CD49d -Tregs are free of contaminating activated T cells and result in purer populations of FoxP3 1 Tregs. 37 The overall frequency of Tregs (regardless of the panel used for their definition) remained stable over time after transplantation, as shown in Supporting Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further characterize Tregs and their subpopulations, groups were defined on the basis of the surface markers CD45RA and CCR7, and naive Tregs were additionally described as CD45RA + CD62L + . HLA‐DR + Tregs have been previously described as a functionally distinct population with a high suppressive effect that might play a role in organ rejection . Additionally, earlier publications have shown that CD49d – Tregs are free of contaminating activated T cells and result in purer populations of FoxP3 + Tregs …”
Section: Resultsmentioning
confidence: 99%